Free-radical fluorescence emissions induced by 1,030 nm femtosecond laser filamentation in ethanol flame - Li, Ziting; Chen, Jinming; Liu, Zhaoxiang; Li, Yi; Chu, Yuxi; Chen, Ye; Cheng, Ya (Frontiers in Physics, 2022)
We experimentally investigate clean optical emissions from multiple combustion intermediates including free radicals C2, CH, and CN at multiple wavelengths induced by ultrashort 1030-nm laser pulses. We systematically study the evolution of the fluorescence emissions induced by femtosecond laser filament in the combustion field with the parameters such as the laser pulse energy, pulse duration and focal length. Comparing with the previous work, we promote that the fluorescence emissions of the combustion product can be manipulated effectively by controlling the femtosecond laser characteristics including pulse energy, duration and the focusing conditions. This process helps to optimize its signal-to-noise ratio, which providing a further application of the femtosecond laser pulses to sense the combustion intermediates.